Innovative business by utilizing avocado seeds that can become economic sources especially for students - Erlyna Wida Riptanti; Tika Ayu Ramadhani; Wahyuningrum Wahyuningrum; Wawang Widiyantoro (Future Science, 2018)
Entrepreneurship is a creative and inovative ability, keen to see opportunity which is always open for every positive input and change, and able to bring business to keep growing and have value. Entrepreneurship is a seeking for opportunity process that faced by each people in ordinary life. The opportunity can by utilizing leftover material around, that converted to something new and useful enough for public necessity. Entrepreneurship with the background of optimalizing the potential of avocado seed that mostly less used by people, can be used as opportunity for independent business. The purpose of this entrepreneurship is to build an innovative business by utilizing avocado seeds that can be a source of economy, especially for students. Avocado seeds processed into a new product that has more added value, which is a product mask powder branded MIKAT (avocado seed mask) for facial skin The implementation methods is divided into 3 phases which is preparation, production and market survey phase; mass production and promotion phase; and also marketing and evaluation phase. The total prices of selling masker for 1 month is Rp 800.00,00 with the cleaness profit is Rp 366.765,00 with production outcome is Rp 433.240,00